DINAMIKA ORGANISASI PEREMPUAN HIMPUNAN MAHASISWA ISLAM CABANG PEKANBARU PERIODE 2008-2011 - Andriani, Defi; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The question of violence against women, discrimination , marginalization, subordination and dual role has been the experience of women in any country and social class with anywhere . So the issue of women can be categorized as strategic issues . therefore keputrian department presence is not enough to do it then takes an own organization , known under the name HMI KOHATI .KOHATI as one of the specialized agencies of the board HMI is the most often suffer from structural dynamics , among which are: to issue liquidation compared to other specialized agencies . The argument is usually acute moment of moments HMI to the congress and the National Consultative KOHATI . Beyond the issue of dissolution , KOHATI also stained with various issues KOHATI function in the body HMI , is related to the function ex officio KOHATI in the structure of the management of HMI .Therefore, based on the phenomenon should probably take title author